(untitled) (Journal of the College of Basic Education, 2023)
The current research aims to identify the anticipatory motivation of kindergarten students, and the research relied on the descriptive approach, and the research sample consisted of (400) students from the kindergarten department at Al-Mustansiriya University / College of Basic Education. The theories and previous studies related to the subject of their research, as the proactive motivation scale in its final form included (40) items, and the two researchers verified the standard psychometric characteristics of the tool. The two researchers reached the following results:1- The students of the kindergarten department are distinguished by proactive motivation.2- There are no statistically significant differences in the anticipatory motivation of the kindergarten students due to the variable of the school stage.Keywords: anticipatory motivation, kindergarten students.